COVID-19 Vaccination: Prevalence and Associated Factors among Students and Staff (A Case of Islamic University in Uganda) - Naziru Rashid; Nabukeera Madinah; Nazziwa Aisha; Aleemu AbdulMujeeb Babatunde; Ummusalam Araphat; Kyejjusa Yusuf (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: COVID-19 Vaccination is an important control measure for the spread of covid -19 with in Academic Institutions. This study aimed to investigated the Prevalence of COVID-19 Vaccination and associated factors among University Students and staff.Subjects and Method: This was a cross-sectional study conducted at Islamic University, Uganda, from July to October 2021. A number of 397 students and staff of IUIU were selected purposively. The dependent variable was vaccination status. The independent variables were age, gender, education status, source of income, religion, marital status, nationality risk perception. Data were collected using an online google form sent via emails WhatsApp and ERP and analyze using Chi-square.Results: There were 397 participants, the modal age was 16-25 years 233 (58.7%) were male, the prevalence of COVID-19 Vaccination was 20.4 % (81). Factors such as age (OR= 0.59; 95% CI= 0.25 to 1.37; p<0.001), Gender (OR= 0.59; 95% CI= 1.06 to 3.00; p=0.026), marital status (OR= 1.55; 95% CI= 0.20 to 0.56; p<0.001) were associated with uptake of COVID-19 vaccination.Conclusion: The Study found a low Prevalence of COVID-19 Vaccination (20.4%) among students and staff at IUIU, and a number of factors presented above were responsible for this. More Education and sensitization on the importance of Vaccination is still needed. A follow up study on the same should be done after full opening of academic institutions.Keywords: prevalence, COVID-19, vaccination, factor, studend and staff, UgandaCorrespondence:Naziru Rashid. University Medical Officer. Islamic University in Uganda (IUIU). Soroti, Mbale Rd, Mbale, Uganda. Email: nazrash2013@gmail.com. Mobile phone: +256702038 741Journal of Health Promotion and Behavior (2022), 07(01): 18-27 DOI: https://doi.org/10.26911/thejhpb.2021.07.01.03